2021
DOI: 10.1371/journal.pone.0252025
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of preterm birth in nulliparous women using logistic regression and machine learning

Abstract: Objective To predict preterm birth in nulliparous women using logistic regression and machine learning. Design Population-based retrospective cohort. Participants Nulliparous women (N = 112,963) with a singleton gestation who gave birth between 20–42 weeks gestation in Ontario hospitals from April 1, 2012 to March 31, 2014. Methods We used data during the first and second trimesters to build logistic regression and machine learning models in a “training” sample to predict overall and spontaneous preterm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 57 publications
0
25
2
1
Order By: Relevance
“…31,32 Some reported associations were absent in our study, including maternal age, BMI, maternal height, smoking during pregnancy, alcohol use, maternal medical history, ART, previous miscarriages or terminations of pregnancy, short cervical length. 7,10,30,33,34 Unfortunately, our study was underpowered to detect these associations. This is most likely for the associations with small ORs found in other studies (e.g., maternal age and BMI).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…31,32 Some reported associations were absent in our study, including maternal age, BMI, maternal height, smoking during pregnancy, alcohol use, maternal medical history, ART, previous miscarriages or terminations of pregnancy, short cervical length. 7,10,30,33,34 Unfortunately, our study was underpowered to detect these associations. This is most likely for the associations with small ORs found in other studies (e.g., maternal age and BMI).…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies among nulliparous women identified several of the associated factors with sPTB found in our cohort, such as socioeconomic deprivation, ethnicity, marital status, vaginal bleeding during early pregnancy. 7,10,[29][30][31] A Danish study showed that vaginal bleeding during the first pregnancy also increased the risk of PTB in a second pregnancy, but this finding was not confirmed in a smaller study executed in the United States of America. 31,32 Some reported associations were absent in our study, including maternal age, BMI, maternal height, smoking during pregnancy, alcohol use, maternal medical history, ART, previous miscarriages or terminations of pregnancy, short cervical length.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In other words, probability is directly related to the cost function and thus the algorithm produces unbiased probability estimates [ 62 ]. This means Lreg model had returned a well calibrated predictions as it directly optimizes the “Log loss” (also known as cross-entropy loss) [ 63 , 64 ]. In other words, the tested models returned somewhat a biased probabilities compared to that shown by logistic regression.…”
Section: Discussionmentioning
confidence: 99%